2015
DOI: 10.1177/0267659115590625
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio: a novel marker for predicting hospital mortality of patients with acute type A aortic dissection

Abstract: The novel inflammatory marker NLR may be used to predict worse outcomes and hospital mortality in patients with AAD treated by surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 34 publications
1
44
1
Order By: Relevance
“…In previous studies, an increase in NLR level was shown to be associated with increased mortality in patients with Stanford type B and DeBakey type 1 acute aortic dissection (15,16). In this study, although higher NLR values were obtained in DeBakey type 2 cases compared to other types, the difference was not statistically significant (p=0.549).…”
Section: Discussioncontrasting
confidence: 74%
“…In previous studies, an increase in NLR level was shown to be associated with increased mortality in patients with Stanford type B and DeBakey type 1 acute aortic dissection (15,16). In this study, although higher NLR values were obtained in DeBakey type 2 cases compared to other types, the difference was not statistically significant (p=0.549).…”
Section: Discussioncontrasting
confidence: 74%
“…Elevation of the WBC count is a well-known acute phase reaction in patients with aortic dissection and several studies have already investigated the effect of WBC count elevation in ATAAD [12][13][14]. Fan et al used a cut-off value of 11.0 x 10 3 /μL to define WBC elevation and reported that in-hospital mortality was worse for patients with an elevated WBC count (n = 216) than for patients with a normal WBC count (n = 354) [14].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ATAAD, hemodynamic instability can occur as a result of cardiac tamponade or aortic insufficiency, and emergency aortic repair under cardiopulmonary bypass induces a strong perioperative inflammatory response, making investigation of the early inflammatory response more complicated. Nevertheless, there is evidence that systemic inflammation characterized by elevation of the white blood cell (WBC) count [12][13][14] or an increased neutrophil/lymphocyte ratio [13,15,16] influences outcomes in patients with ATAAD. Although biomarkers of disordered coagulation and fibrinolysis D-dimer and fibrin degradation products have been well studied in relation to acute aortic dissection [17][18][19], WBC count elevation and its etiology in cases of acute aortic dissection have not been fully elucidated, and the relation between WBC elevation and dissection morphology is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[14] However, there is a growing interest in bedside risk assessment for in-hospital death, and in many current research studies, several biomarkers of vascular damage, thrombosis, and inflammation have been evaluated as contributors in the diagnosis of AAD or as risk prediction tools. [1617181920]…”
Section: Discussionmentioning
confidence: 99%
“…[29] also revealed that patients who had serious clinical symptoms and developed disease progression had higher inflammatory cell activity in the aortic wall than asymptomatic and clinically stable patients. More interestingly, there is now substantial evidence to suggest that increased circulating inflammatory markers such as CRP,[18] neutrophil-to-lymphocyte ratio,[19] and WBC count[20] could predict clinical events in patients with acute TAAD, especially death during hospitalization.…”
Section: Discussionmentioning
confidence: 99%